Advances in design for inclusion : proceedings of the AHFE 2017 International Conference on Design for Inclusion, July 17-21, 2017, the Westin Bonaventure Hotel, Los Angeles, California, USA /: proceedings of the AHFE 2017 International Conference on Design for Inclusion, July 17-21, 2017, the Westin Bonaventure Hotel, Los Angeles, California, USA. ([2018]) - Unknown
No abstract available